Sustainable Interoperability Framework for supporting Negotiation Processes - Coutinho, C.; Cretan, A.; Jardim-Goncalves, R. (Proceedings of the 6th International Conference on Interoperability for Enterprise Systems and Applications (I-ESA 2012), 2012)
As globalization leads companies to continuously interoperate and seek new partnerships, current interoperability becomes very fragile and sensitive to external factors, making it easy to break loose; the more complex it is, the easier it is to get lost and the harder it is to be regained. This paper details a framework to model and support sustainable interoperability of parallel and concurrent negotiations among organizations acting in the same industrial market, using a model-driven, cloud-based, service-oriented platform with the purpose to model a dynamic environment where multi-attribute and multi-participant negotiations are racing over a set of heterogeneous resources.